The sources and limitations of subjectivity - Mazur, Stanisław (Journal of Public Governance, 2014)
The aim of this paper is to draw attention to a long tradition of understanding the sources and limitations of subjectivity and to discuss the rich legacy of philosophical thought on the subject.